Protestantism existentialist modernization in Paul Tillih’s theology - Shevchenko, Serhii (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2015)
The article analyzes the methodological problem of the application of Paul Tillih’s existentialist categorial-conceptual apparatus to update the theological interpretation of Christian proclamation today. We consider the specificity of definition views of Tillih in the foreign and Ukrainian historical and philosophical thought, particularly in the context of existential and existentialist tradition. Disclosed features existentialism impact on the process of modernizing the example of Protestantism Tillih’s "theology of culture" and "systematic theology". We give the definition and characteristics of the main categories of Tillih’s theology, which formed under the influence of existentialism